How important is water endowment for trade in agricultural products? - Mat Ghani, Gairuzazmi (The Empirical Economics Letters, 2008)
Water is an important input for the production of agricultural products. Hence, following the Heckscher-Ohlin model and the virtual water hypothesis, relatively water abundant countries will have comparative advantage in agricultural products. We show that water endowment does play a role in determining agricultural products’ comparative advantage, especially for net importing countries.